MAKING HIGHT ANTIOXIDANT MIX FRUIT POWDER WITH COMPOSITION VARIATIONS FRUIT AND DRYING TEMPERATURE - Anitarakhmi; Amalia; Laurita; Rovita; Angela; Dinda; Minah, Faidliyah Nilna; Pricilia, Anastasia; Mufidah, Azmi (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2022)
Making a drink mix fruit from the fruit of the banana ambon, california papaya, pumpkin and Solanum betaceum can be a way to enhance antioxidant content of their products, and will raise the value of fondness of the community towards it. This study aims to determine the right formula of the variation of composition fruit and temperature levels drying against anti oxidant and know received the community in power fruit drink mix. Methods used to making a drink mix fruit that is a method in which a Foam Mat Drying. Based on an analysis of the vitamin C the best conditions exist to variation composition fruit 50% of Solanum betaceum. While for antioxidant content IC50 the best conditions exist to variation composition fruit 50% of banana ambon at a temperature of 50 oC. The temperature drying affecting the womb IC50 antioxidant vitamin C and fruit resulting mix to the liqueurs. Based on the is the hedonic organoleptic, can was received by the fruit drink mix for its shade from variations composition 50% of pumpkin (50 oC), the scent of 50% of pumpkin (70 oC), and the sense of 25% respectively fruit (50 oC). So it can be concluded that variations composition fruit that is produced with composition of the 50% of pumpkin.